INFLUENCE OF ALLOYING CONDITIONS ON THE PROPERTIES OF WHITE CAST IRON - NODIR TURAKHODJAEV; SARVAR TURSUNBAEV; DILYARAM UMAROVA; MUNIRA KUCHKOROVA; AZAMAT BAYDULLAEV (International Journal of Innovations in Engineering Research and Technology, 2021)
The article highlights the results of studying the influence of alloying conditions on the quality of white cast iron. In the experiment, the doping conditions were carried out in various ways. Based on the conducted experiments, the results of the study were summarized.